Biopsy interpretation of the lung - Suster, David Ilan (Biopsy interpretation series., 2021)
"Biopsy Interpretation of the Lung aids pathologists in accurately evaluating disease processes. It includes detailed chapters on interstitial lung disease, lung cancer, and neuroendocrine tumors. Organized by traditional disease groups, Biopsy Interpretation of the Lung provides a solid approach to formulating surgical and medical decisions."--